Morte e linguagem: um estudo de inquérito às quatro confidências, de Maria Gabriela Llansol - Pereira, Nathália Gonçalves Fernandes (2009)
The analysis of Inquiry to the four confidences, Diary III, by Maria Gabriela Llansol, from its critical fortune, with the purpose of investigating the process of resurrection present in the textual figure of Vergílio Ferreira, emphasizing death, inherent concept to philosophy and to literary work, and its relation to language. Description of the genre diary as self-writing and observation of the transformation of the work in signography study, focusing autobiographical procedures related to the author s everyday life.